Estimating number of workers potentially at risk of exposure to hardwood dust in certain industrial sectors in Italy using a national register - Scarselli, Alberto; Di Marzio, Davide (La Medicina del Lavoro, 2014)
Background: Hardwood dust is a well-known human carcinogen and its use is common in several economic activities. Objectives: The aim of this study was to assess the extent of occupational exposure to hardwood dust in certain sectors of Italian industry. Methods: Information on occupational exposures was collected from enterprise exposure registers that must by law be reported to the National Workers’ Compensation Authority, as at 31 December 2011. Data stored in the database included economic activity sector, work force size and exposed workers. The number of workers potentially exposed was estimated for some of the industrial sectors from national occupational statistics in Italy. Results: The economic sector with the highest number of potentially exposed workers to hardwood dust was that classified as the manufacture of other wooden furniture with 15,760 men and 2,771 women, while the highest percentage of enterprises that had sent data (according to the ISTAT 2001 census) was in building and repair of non-metallic ships (21%). Conclusions: The systematic recording of occupational exposures is a source of data that permits recognition of high risk situations and aids exposure assessment for epidemiological studies.